KEKUATAN PEMBUKTIAN AKTA NOTARIAL DALAM PENYELESAIAN PERKARA JUAL BELI TANAH (STUDI PUTUSAN NO. 124 PK/PDT/2015) - Edmond Putra; Hasni . (Fakultas Hukum Universitas Tarumanagara, 2018)
Agrarian law in the broad sense is the entire rules of law both written and unwritten governing the earth, water and within certain limits also space and natural wealth contained therein.as well as in a process of buying and selling land, the parties will certainly first make an agreement between the parties before the buying and selling of land. in this case the binding sale and purchase agreement, which serves as a proof tool at the time of the litigants in court. but in this case despite the existence of such strong and perfect evidence, the judge does not decide the case carefully and fairly, the reason is that one of the parties in this case feels aggrieved by the verdict granted by the judge, for what has been written in binding agreements of sale and purchase and addendum are not used as a basis by the judge in deciding the case. then it is with the writing of this journal, it is expected that this journal can be the aspirations and opinions in examining a civil case, so it is for the future if there is a similar case can be used as a reference for the enforcer the law to be more careful and study the case being handled it, the purpose is to avoid the occurrence of judges who are less aware of the knowledge of the case being handled, so that it affects the quality of decisions made by it.